Exploring the promotional effect of transition metals (Cr and V) on the catalytic activity of MgO for glycerol carbonate synthesis - Pradhan G.; Jaiswal S.; Sharma Y.C. (My University, 2025)
This work reports the reactivity of Mg containing spinels like MgCr2O4 and MgV2O4 for synthesis of glycerol carbonate from bio-glycerol on the basis of their structural, morphological and catalytic properties. Metal oxides having spinel structure exhibit very amazing catalytic properties due to their unique crystal structure and multiple properties like extended surface area, higher basic strength and multiple redox centres. Several characterization techniques like XRD, XPS, TGA, Raman, N2 adsorption-desorption and SEM-EDX study confirmed the successful synthesis of spinels. Amongst MgCr2O4 (MCO) and MgV2O4(MVO), MCO proved to be very active and contributed excellent catalytic activity towards glycerol valorisation i.e. 98% conversion of glycerol at mild reaction conditions than that of MVO (82% conversion of glycerol). MCO was highly efficient than that of MVO because of its higher basicity, higher crystallite size which are the fundamental properties for enhancing the catalytic activity of heterogeneous catalysts. From environmental point of view MCO was very flexible, efficient and environmentally friendly catalyst as having ideal E-factor, PMI, and AE values. Overall description concluded that the metal oxide spinels are quite active and enormously applied in glycerol biorefinery in lab scale as well as industrial scale. © 2022